Transdifferentiation of Human Circulating Monocytes Into Neuronal-Like Cells in 20 Days and Without Reprograming - Bellon, Alfredo; Wegener, Amelie; Lescallette, Adam R.; Valente, Michael; Yang, Seung-Kwon; Gardette, Robert; Matricon, Julien; Mouaffak, Faycal; Watts, Paula; Vimeux, Lene; Yun, Jong K.; Kawasawa, Yuka Imamura; et al. (Frontiers in Molecular Neuroscience, 2018)
Despite progress, our understanding of psychiatric and neurological illnesses remains poor, at least in part due to the inability to access neurons directly from patients. Currently, there are in vitro models available but significant work remains, including the search for a less invasive, inexpensive and rapid method to obtain neuronal-like cells with the capacity to deliver reproducible results. Here we present a new protocol to transdifferentiate human circulating monocytes into neuronal-like cells in 20 days and without the need for viral insertion or reprograming. We have thoroughly characterized these monocyte-derived neuronal-like cells (MDNCs) through various approaches including; single cell mRNA sequencing, flow cytometry, electrophysiology, western blots, immunofluorescence and pharmacological techniques. These MDNCs resemble human neurons early in development, express a variety of neuronal genes as well as several neuronal proteins and also present electrical activity. In addition, when these neuronal-like cells are exposed to either dopamine or colchicine, they respond similarly to neurons by retracting their neuronal arborizations. More importantly, MDNCs exhibit reproducible differentiation rates, arborizations and expression of dopamine 1 receptors on separate sequential samples from the same individual. To provide context and help researchers decide which in vitro model of neuronal development is best suited to address their scientific question, we compare our results with those of other in vitro models currently available and expose advantages and disadvantages of each paradigm.